THE PECULIARITIES OF BIOLOGY AND HARMFULNESS OF THOMASINIANA OCULIPERDA RUBS. AND PROTECTION METHODS AGAINST IT OF APPLE TREES’ SAPLING IN THE CENTRAL STEP ZONE OF UKRAINE - Яновський, Ю. П.; Cуханов С. В.; Гричанюк, В. П. (Scientific Progress & Innovations, 2015)
The results of studies were showed to clarify the biological peculiarities, harmfulness of apple leaf curling midge of apple trees’ sapling and efficacy of insecticides in control of pest infestation in Forest-Steppe zone of Ukraine. It is established, that larva overwinters in the soil on the depth of 4-5 cm, their revival is observed at the end of 1st till the end of second decade of April and pupation – in late second – early third decade of April. Adult female’s flights take place in the second decade of May – first decade of June. In 8–10 days larva appears, which damage 29,8–37,7 % of grafting buds. During the vegetation period the pest is developing by three generations. For one generation of pest’s development need the sum of effective temperature from 274,3°С to 290,6°С (the lower threshold of the temperature is 15,6°С). The technical efficiency of products application in protection of this crop against this pest is studied. It is established that for decreasing of its harmfulness it needed to apply the following insecticides Mospilan, RP (0,2 kg/hа), Calipso 480 SC, (0,25 l/hа), Sumition, КЕ (2,5 l/hа), Hlovis СК ( 1,5 l/hа), Dursban 480, SC (2,0 l/hа), Zolon 35, KE (3,0 l/hа), Lannate 20,RК (1,2 l/hа) and Pirineks 480, КЕ (2,0 l/hа).